New chromium(III)-based catalysts for ethylene oligomerization - Jacek Malinowski (Nature Portfolio, 2020)
Abstract The report focuses on the new precatalysts for ethylene oligomerization. The five chromium(III) complex compounds containing the following ligands: dipicolinate anion, oxalate anion, 5-aminopyridine-2-carboxylate anion, 2,2′-bipyridine and 4,4′-dimethoxy-2,2′-bipyridine have been examined towards catalytic activity for ethylene oligomerization. The chromium(III) complexes have been activated by modified methylaluminoxane. The obtained oligomers have been investigated by MALDI-TOF–MS, thermal analysis and infrared spectroscopy. The results revealed that the examined chromium(III) complexes are highly active catalysts for ethylene oligomerization. The values of catalytic activities of the examined complexes are in the range 1860 – 3798 g∙mmol-1∙h-1∙bar-1.